Does Affordability Status Matter in Who Wants Multifamily Housing in Their Backyard? - Eriksen, Michael D.; Yang, Guoyang (The Review of Economics and Statistics, 2025)
Abstract We provide evidence that similar price effects occur from new multifamily rental housing on surrounding owner-occupied property values regardless of whether the development was subsidized. These effects were on average negative in higherincome communities, but became either non-distinguishable from zero or positive in higher-income communities with sufficient population density. These results imply that previous opposition to all new rental housing by homeowners is misguided as developments could raise property values in some higher-income neighborhoods.